2004
DOI: 10.1038/sj.eye.6700747
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy progression and visual outcome after phacoemulsification in South-Asian and Afro-Caribbean patients with diabetes

Abstract: Purpose To determine diabetic retinopathy or maculopathy progression and visual outcome following phacoemulsification in South-Asian and Afro-Caribbean patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Because most patients were referred from other hospitals, accurate data on previous laser treatments, the duration of CSME, and systemic control of diabetes were not available and thus could not be included in the statistical analysis. In our study, the rate of progression of DR in the control group was 45.45%, which is similar to that reported by Chatterjee et al 27 in British Afro-Caribbean diabetic patients having phacoemulsification. Although direct comparison between studies is difficult, our study found a significant reduction in the rate of progression of DR in eyes that received an intravitreal injection of bevacizumab.…”
Section: Discussionsupporting
confidence: 92%
“…Because most patients were referred from other hospitals, accurate data on previous laser treatments, the duration of CSME, and systemic control of diabetes were not available and thus could not be included in the statistical analysis. In our study, the rate of progression of DR in the control group was 45.45%, which is similar to that reported by Chatterjee et al 27 in British Afro-Caribbean diabetic patients having phacoemulsification. Although direct comparison between studies is difficult, our study found a significant reduction in the rate of progression of DR in eyes that received an intravitreal injection of bevacizumab.…”
Section: Discussionsupporting
confidence: 92%
“…Ultimately, 8 studies were included in the meta-analysis. 1,2,4,[9][10][11][12][13] The number of patients in the 8 studies ranged from 30 to 119, and number of eyes ranged from 30 to 180. The mean or median age ranged from 66.4 to 76 years, and the proportion of males ranged from 32% to 79% (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Chatterjee et al 8 present an original piece of work assessing diabetic retinopathy and maculopathy progression along with visual outcome following phacoemulsification cataract extraction in South-Asian and Afro-Caribbean patients who are type II diabetics. 8 There results show that 86.7% achieved a final postoperative visual acuity of 6/12 or better. More importantly, there was no statistical difference in the number of operated and fellow eyes that developed progression of retinopathy or maculopathy.…”
mentioning
confidence: 84%
“…The reported rate of progression of diabetic retinopathy following phacoemulsification in the general diabetic population ranges between 20 and 34%. 4,[9][10][11] In Chaterjee's study, 8 23.4% of patients showed either symmetric or asymmetric progression at a mean follow-up of 12.4 months. The results of this study suggest that uncomplicated phacoemulsification in South-Asian and Afro-Carribean patients with diabetes is associated with a favourable postoperative visual outcome that is comparable with the results of phacoemulsification in the general diabetic population.…”
mentioning
confidence: 99%